A brief history of seven killings - James, Marlon, 1970- (London : Oneworld, 2014)
"From the acclaimed writer of The Book of Night Women comes a masterful novel framed as a fictional oral history that explores the events and characters surrounding the attempted assassination of Bob Marley during the political turmoil on Jamaica in the late 1970s"--
AAL
Man Booker Prize for Fiction, 2015.
Keywords: Marley, Bob -- Assassination attempts -- Fiction; Assassins -- Fiction; Oral history -- Fiction; Reggae musicians -- Jamaica -- Fiction; Rastafarians -- Jamaica -- Fiction; FICTION / Literary; FICTION / Historical; Jamaica -- History -- 1962- -- Fiction; New York (N.Y.) -- History -- 20th century -- Fiction; Historical fiction